2014
DOI: 10.1007/s00408-013-9551-8
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Assessment of High Versus Low Levels of Fractional Exhaled Nitric Oxide Among Children with Asthma and Atopy

Abstract: Purpose Fractional exhaled nitric oxide (FeNO) has emerged as an important biomarker in asthma. Increasing evidence points to atopy as a confounding factor in the interpretation of elevated FeNO. We conducted a longitudinal study to understand the clinical significance of FeNO as an inflammatory biomarker. Methods We identified 19 children aged 13–15 years at baseline with a significant elevation in FeNO ≥ 80 parts per billion (ppb) and randomly selected a group of children of similar age with a moderate ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 28 publications
2
11
1
1
Order By: Relevance
“…This increase has been associated with the severe asthma atopic phenotype. In our study, we find a weak, marginal, but non‐significant correlation between FE NO values and the FEV 1 /FVC ratio (the higher the FE NO value the lower the FEV 1 /FVC ratio); this result is similar to that found by Elmasri in his study on FE NO levels in children with asthma and atopy . We do not have reference values for FE NO at the altitude of Bogotá (located at 2640 meters).…”
Section: Discussionsupporting
confidence: 79%
“…This increase has been associated with the severe asthma atopic phenotype. In our study, we find a weak, marginal, but non‐significant correlation between FE NO values and the FEV 1 /FVC ratio (the higher the FE NO value the lower the FEV 1 /FVC ratio); this result is similar to that found by Elmasri in his study on FE NO levels in children with asthma and atopy . We do not have reference values for FE NO at the altitude of Bogotá (located at 2640 meters).…”
Section: Discussionsupporting
confidence: 79%
“…One study of 52 children aged 5–36 months demonstrated significantly higher FeNO levels in children with a positive asthma predictive index (API) compared to those with a negative API, although the median levels in both groups were low at 12.5 and 5.6 ppb, respectively [34]. FeNO levels have been described to be higher in allergic or atopic asthma compared to nonallergic asthma [45], but are also elevated in children who have allergic sensitization as demonstrated by positive skin-prick testing or aeroallergen-specific IgE [32,35,43]. FeNO levels have been shown to be higher in children with allergic sensitization or atopy and no asthma compared to nonallergic asthma [32,35,45], and have been found to be higher in children both with treated and untreated asthma than in healthy nonatopic children [54].…”
Section: Feno and Diagnosis Of Asthmamentioning
confidence: 99%
“…Die Bestimmung des FeNO kann bei Erwachsenen und bei Kindern hilfreich sein bei der Sicherung der Asthmadiagnose, insbesondere, wenn die Messung beim Patienten ohne regelmäßige ICS-Therapie und im obstruktionsfreien Intervall durch-geführt wird [160]. Bei allergischem Asthma wurden höhere FeNO-Werte als bei nicht allergischem Asthma gefunden [161]. Niedrige FeNO-Werte allein erlauben dagegen nicht den differenzialdiagnostischen Ausschluss von Asthma bronchiale [162].…”
Section: Stickstoffmonoxid (Feno) In Der Ausatemluftunclassified